Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To solve the equation [tex]\(\log (15 - 5x) - \log (3x - 2) - 2 = 0\)[/tex] for [tex]\(x\)[/tex], let's follow these steps:
1. Simplify the Logarithmic Expression:
Use the properties of logarithms to combine the logs:
[tex]\[ \log (15 - 5x) - \log (3x - 2) = \log \left( \frac{15 - 5x}{3x - 2} \right) \][/tex]
Hence, the equation becomes:
[tex]\[ \log \left( \frac{15 - 5x}{3x - 2} \right) - 2 = 0 \][/tex]
2. Isolate the Logarithm:
Add 2 to both sides of the equation:
[tex]\[ \log \left( \frac{15 - 5x}{3x - 2} \right) = 2 \][/tex]
3. Convert Logarithmic Form to Exponential Form:
Recall that if [tex]\(\log_a (b) = c\)[/tex], then [tex]\(a^c = b\)[/tex]. Here, the logarithm is in base 10 by default:
[tex]\[ 10^2 = \frac{15 - 5x}{3x - 2} \][/tex]
Therefore:
[tex]\[ 100 = \frac{15 - 5x}{3x - 2} \][/tex]
4. Solve the Resulting Equation:
Multiply both sides by [tex]\((3x - 2)\)[/tex] to clear the fraction:
[tex]\[ 100(3x - 2) = 15 - 5x \][/tex]
Expand and combine like terms:
[tex]\[ 300x - 200 = 15 - 5x \][/tex]
Add [tex]\(5x\)[/tex] to both sides:
[tex]\[ 300x + 5x - 200 = 15 \][/tex]
Combine like terms:
[tex]\[ 305x - 200 = 15 \][/tex]
Add 200 to both sides:
[tex]\[ 305x = 215 \][/tex]
Finally, divide both sides by 305:
[tex]\[ x = \frac{215}{305} \][/tex]
5. Simplify the Fraction (if needed, though not necessary if the direct answer is known):
Reduce the fraction:
[tex]\[ x = \frac{43}{61} \][/tex]
Given this detailed step-by-step solution, the value of [tex]\( x \)[/tex] that satisfies the equation [tex]\(\log (15 - 5x) - \log (3x - 2) - 2 = 0\)[/tex] is:
[tex]\[ x = \frac{43}{61} \][/tex]
1. Simplify the Logarithmic Expression:
Use the properties of logarithms to combine the logs:
[tex]\[ \log (15 - 5x) - \log (3x - 2) = \log \left( \frac{15 - 5x}{3x - 2} \right) \][/tex]
Hence, the equation becomes:
[tex]\[ \log \left( \frac{15 - 5x}{3x - 2} \right) - 2 = 0 \][/tex]
2. Isolate the Logarithm:
Add 2 to both sides of the equation:
[tex]\[ \log \left( \frac{15 - 5x}{3x - 2} \right) = 2 \][/tex]
3. Convert Logarithmic Form to Exponential Form:
Recall that if [tex]\(\log_a (b) = c\)[/tex], then [tex]\(a^c = b\)[/tex]. Here, the logarithm is in base 10 by default:
[tex]\[ 10^2 = \frac{15 - 5x}{3x - 2} \][/tex]
Therefore:
[tex]\[ 100 = \frac{15 - 5x}{3x - 2} \][/tex]
4. Solve the Resulting Equation:
Multiply both sides by [tex]\((3x - 2)\)[/tex] to clear the fraction:
[tex]\[ 100(3x - 2) = 15 - 5x \][/tex]
Expand and combine like terms:
[tex]\[ 300x - 200 = 15 - 5x \][/tex]
Add [tex]\(5x\)[/tex] to both sides:
[tex]\[ 300x + 5x - 200 = 15 \][/tex]
Combine like terms:
[tex]\[ 305x - 200 = 15 \][/tex]
Add 200 to both sides:
[tex]\[ 305x = 215 \][/tex]
Finally, divide both sides by 305:
[tex]\[ x = \frac{215}{305} \][/tex]
5. Simplify the Fraction (if needed, though not necessary if the direct answer is known):
Reduce the fraction:
[tex]\[ x = \frac{43}{61} \][/tex]
Given this detailed step-by-step solution, the value of [tex]\( x \)[/tex] that satisfies the equation [tex]\(\log (15 - 5x) - \log (3x - 2) - 2 = 0\)[/tex] is:
[tex]\[ x = \frac{43}{61} \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.